Experimental study of radiation heat transfer coefficient of diffusion flames - Ga, Bui Van; Tuy, Le Van; Vang, Huynh Ba; Lu, Le Van; Linh, Nguyen Ngoc (Vietnam Journal of Mechanics, 2007)
Basing on analysis of flame pictures given by visioscope by two-color method, the paper presents evolution of radiation heat transfer coefficient \(ε_s\) of soot in diffusion flames in air, in furnace and in combustion chamber of Diesel engine. \(ε_s\) reaches respectively its maximal value of 0.15; 0.30 and 0.45 in regions of maximal soot fraction of the three above flames.